A vagon - Zelki, János (Hungary, 2007)
The film discusses one of the most horrible aspects of the Holocaust: the delivery of the deported people to the lagers, the days spent in the wagons. The Wagon gives voice to those who have experienced this inhumane form of transportation.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films